Carbon nanotubes: a review on future generation nano device - Farhana, Soheli; Alam, A. H. M. Zahirul (IDOSI Publications, 2014)
This paper provides an overview of carbon nanotubes (CNTs). The fundamental relations leading the geometry of carbon nanotubes are reviewed and explicit examples are presented. A framework is given for the symmetry properties of carbon nanotubes. The implications of symmetry on the electronic structure of 1D carbon nanotube systems are considered. The corresponding properties of hexagonal coordinate system and electrical properties of carbon nanotubes are also discussed.